Can the Tripartite Rubber Council manipulate international rubber prices? - Thomas Kopp; Bernhard Dalheimer; Zulkifli Alamsyah; Mirawati Yanita; Bernhard Brümmer (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2019)
Abstract: In contrast to the trend of a generally increasing liberalization of markets, agriculture remains one of the most protected sectors. In globally distributed production networks the effects of sector specific policies may spill over to other sectors and other countries. While the effects of these policy spill-overs are likely to be substantial, both conceptual and empirical work is surprisingly limited in the literature. This paper suggests an extension of the Gardner Model by two policy interventions to theoretically predict effects of exogenous policy shocks in one input market on price relations towards its substitutes. The economic model is then applied to the markets for natural and synthetic rubber which is an insightful example because the natural rubber market has been dominated by three big exporters who have collectively introduced policies to gain price control for decades. Results of a vector error correction analysis indicate that prices of natural rubber, synthetic rubber and crude oil are cointegrated. Both policies under consideration an export tax and several measures to restrict supply partly detached the natural from the synthetic rubber price in international markets. However, one of the policy measures might have produced effects detrimental to the intended targets.
urn:nbn:de:gbv:7-webdoc-3995-6
Keywords: 330; Price Transmission Analysis; VECM; Tripartite Rubber Council; Indonesia; Thailand; Malaysia; Policy Interventions